Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0190009
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral nephrectomy diminishes ischemic acute kidney injury through enhanced perfusion and reduced pro-inflammatory and pro-fibrotic responses

Abstract: While unilateral nephrectomy (UNx) is suggested to protect against ischemia-reperfusion injury (IRI) in the remaining kidney, the mechanisms underlying this protection remain to be elucidated. In this study, functional MRI was employed in a renal IRI rat model to reveal global and regional changes in renal filtration, perfusion, oxygenation and sodium handling, and microarray and pathway analyses were conducted to identify protective molecular mechanisms. Wistar rats were randomized to either UNx or sham UNx i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…2,11,13-17 In addition, it is well known that removal of 1 kidney will stimulate an increase of renal perfusion and GFR with compensatory growth of the remaining kidney. 48 A 1-kidney GFR of 38 and 40 mL/min is below normal range for this size of pigs and represents a state of renal damage when compared with older studies. Frennby et al 49 measured GFR in 1-kidney pigs with reduced renal function and found a median GFR of 30 mL/min/50 kg, supporting this interpretation.…”
Section: Discussionmentioning
confidence: 73%
“…2,11,13-17 In addition, it is well known that removal of 1 kidney will stimulate an increase of renal perfusion and GFR with compensatory growth of the remaining kidney. 48 A 1-kidney GFR of 38 and 40 mL/min is below normal range for this size of pigs and represents a state of renal damage when compared with older studies. Frennby et al 49 measured GFR in 1-kidney pigs with reduced renal function and found a median GFR of 30 mL/min/50 kg, supporting this interpretation.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the increased humoral load and tubular hypertrophy observed in the contralateral kidney may serve as a form of injury that triggers accumulation of macrophages leading to accelerated cystogenesis. Because UNx in wild-type mice does not increase the number of macrophages (44), the accumulation of kidney macrophages upon UNx specifically occurs in the absence of Pkd1. An interesting observation of these studies is data showing that treatment of 1K Pkd1 mice with IRF5 ASO significantly reduced cystic index (i.e., cyst size), but did not affect cyst number.…”
Section: Discussionmentioning
confidence: 97%
“…Unilateral nephrectomy was shown to diminish ischemic AKI through enhanced perfusion and reduced pro-inflammatory and pro-fibrotic responses. 68 The preventive setting revealed a crucial role of CYP-eicosanoids in AKI initiation; however, further studies are needed to prove the therapeutic potential of EET analogues in decreasing renal injury after the ischemic event had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…68 The preventive setting revealed a crucial role of CYP-eicosanoids in AKI initiation; however, further studies are needed to prove the therapeutic potential of EET analogues in decreasing renal injury after the ischemic event had occurred. Unilateral nephrectomy was shown to diminish ischemic AKI through enhanced perfusion and reduced pro-inflammatory and pro-fibrotic responses.…”
Section: Circulating Cyp-eicosanoids In Patients Who Do or Do Not Dmentioning
confidence: 99%